Sugarcane Molasses: Composition, Challenges, and Utilization as an Economically Valuable Raw Material: A Literature Review of Sugarcane Molasses: Composition, Challenges, and Utilization as an Economically Valuable Raw Material - Dewi, Putri Satika; Rasmiyana, Rasmiyana (Universitas Bumigora, 2025)
Sugarcane molasses is a by-product of the sugar production process. Its main components include sugars (such as sucrose, fructose, and glucose), amino acids, and minerals, which offer significant potential for use, particularly in the food sector. This review of the literature was compiled using a descriptive-analytical approach. The findings indicate that the lack of classification based on production stages, as well as negative perceptions toward this by-product, hinder its development and utilization. Recent studies have shown that molasses contains active compounds, including sucrose (48.8 %), fructose (8.45 %), and glucose (7.80 %), along with amino acids and polyphenols, such as diosmin, that provide functional benefits in food and health applications. Moreover, a limited domestic supply poses an additional challenge to the optimal use of molasses. Therefore, innovation in processing and product development is essential, along with increased public awareness of its functional potential. Strengthening the classification system for the types of molasses and enhancing its added value through fermentation or functional food applications could expand industrial opportunities. These efforts are expected to improve the competitiveness of Indonesia's national agro-industry and foster sustainable economic growth.